Analysis of Arabic textbooks for IX grade based on the Merdeka curriculum: تحليل الكتاب المدرسي للغة العربية في الصف التاسع على الأسس المنهج الميرديكا - Qhalby, Misbahul; Yelfi Dewi (Institut Muslim Cendekia, 2025)
The main issue in this study is whether there are differences between the learning materials contained in the ninth-grade Arabic textbooks based on the independent curriculum and the 2024 Learning Outcomes. This research is a literature study using a qualitative approach with content analysis method. The primary data is in the form of Arabic textbooks used in schools, while the secondary data is derived from the 2024 Learning Outcomes document. This study aims to determine the content of Arabic textbooks for ninth grade based on the Merdeka Curriculum. The results of this study indicate that there are differences between the learning materials in Arabic textbooks for ninth grade based on the Merdeka Curriculum and the 2024 learning outcomes, there are deficiencies in the textbooks, and there are errors in the writing of the textbooks. This study recommends revising and developing teaching materials to be more in line with the curriculum and able to meet students' learning needs comprehensively.